Índice glicêmico e carga glicêmica da dieta de mulheres com a síndrome dos ovários policísticos : associações com variáveis metabólicas, antropométricas e de composição corporal - Graff, Scheila Karen (2013)
Objective: To compare glycemic index and load (GI and GL) in the usual diet of PCOS and control women and to investigate whether dietary GI and GL are associated with body composition and anthropometric and metabolic variables across PCOS phenotypes. Design: Cross-sectional study. Setting: University hospital outpatient clinic. Patients: 61 women with PCOS and 44 non-hirsute women with ovulatory cycles. Interventions: Metabolic work-up, biochemical and hormonal assays, assessment of body composition and rest metabolic rate, physical activity (pedometer), and food consumption (food frequency questionnaire). Main outcome measure(s): GI and GL. Results: Mean age was 23.7±6.3 years. The prevalence of obesity was 44.3% in PCOS women and 31.8% in controls. Median GI for the group was 58. PCOS patients with GI>58 had higher BMI, worse metabolic profile, and lower intake of fibers. GI was correlated with BMI in controls and with lipid accumulation product (LAP) in the PCOS group, and was higher in classic PCOS vs. other groups. Conclusions: Dietary GI is increased in PCOS patients, especially in the classic PCOS phenotype. Increased dietary GI is associated with a less favorable anthropometric and metabolic profile in PCOS.